A network to enhance the contributions from the social sciences and humanities to IPBES. Issue 1 (31st December 2022) - Stokland, Håkon B.; Stenseke, Marie; Emery, Marla R.
ABSTRACT: IPBES requires enhanced contributions from the social sciences and humanities in order to meet its mandate and influence policy. However, achieving this has so far proved challenging, notably in the form of a shortage in nominations of experts from these fields. The Social Sciences and Humanities Network (the SSH Network) has been established in an effort to improve this situation. In this short communication, we present challenges identified by the network that hinders increased engagement from scholars from the social sciences and humanities, and strategies developed to overcome them. Among other initiatives, the SSH Network will function as a meeting place for scholars from the social sciences and humanities engaged in IPBES, interested in IPBES, or having IPBES as a study object.